Saldo Comercial De Productos Por Habitante De México, 2001-2014. Un Comparativo Con La Región APEC - Tello, Antonio Favila; Torres, América Ivonne Zamora (European Scientific Journal, ESJ, 2016)
Trade balance per capita is one of the international trade indicators that experts frequently use to evaluate a country’s performance in trade and evaluate its commercial policies. Exports, imports and the trade balance per capita of the 21 APEC countries were calculated for the 2001-2014 period in order to observe and evaluate its recent evolution, especially for the Mexican case. The data used only covered merchandises according to their value in US dollars at constant prices of 2014. Results suggest the existence of trade surpluses in extractive economies such as Brunei, Papua New Guinea and Russia. The exponential growth of exports from Vietnam and China is also demonstrated as well as the outstanding international business activity in Singapore and Hong Kong (which in per capita indicators outweighed all of the other members of APEC). Conditions of trade deficit are detected for powerful economies such as United States and Japan. On the other hand, Mexico shows a balanced condition in this indicator, an important and growing automotive industry and a noteworthy dependence on the US economy.